Egg shell catalyst and chicken waste biodiesel blends for improved performance, combustion and emission characteristics. (15th December 2021) - Ge, Shengbo; Brindhadevi, Kathirvel; Xia, Changlei; Elesawy, Basem H.; Elfasakhany, Ashraf; Unpaprom, Yuwalee; Doan, Hien Van
Graphical abstract: Highlights: Chicken fat waste as the potential biodiesel were examined. Egg shell catalyst effects on the biodiesel blends has been studied. As the concentration of the chicken waste increases BTE and BP reduced. 10% blend reported reduced NOx than neat diesel. Abstract: Over the past few years, the research on the replacement of fossil fuel from inedible oil has been gaining more and more interest owing to the positive approach done on the waste animal fat for the reusable purpose. The performance, emission and combustion characteristics were measured for both diesel and chicken fat biodiesel blends (CFB). A small single cylinder, four stroke, air cooled, combustion ignition engine was used to conduct all tests. The biodiesel was produced by using transesterification process with the chicken eggshell dominated catalyst. The derived catalyst from the waste chicken eggshell was CaO used as a catalyst for the esterification process. The biodiesel blends used for conducting tests were B10 (10% of Chicken fat biooil + 90% diesel), B30 (30% of Chicken fat biooil + 70% diesel), B50 (50% of Chicken fat biooil + 50% diesel) and D100 or B0 (100% diesel). The Brake power (BP), Brake torque, Exhaust Gas Temperature (EGT), Brake specific fuel consumption (BSFC) and emission of CO, CO2, NOx and HC for all fuel blends were calculated and compared with pure diesel B0. All tests were conducted at different engine speed as 1800 rpm, 2000 rpm, 2200 rpm, 2400 rpm and 2600 rpm. From the performance qualities results, the biodiesel blends increased the brake power, BTE, EGT and HRR while reduced the CO, HC and smoke emissions. However, there was a little increment in NOX emission. The CFB is helpful in both overcoming the shortage of fossil fuel and better waste management.